The Effect of Paradoxical Intension Session 1 Logotheraphy on Prisoners Anxiety in LAPAS Kediri - Lingga Kusuma Wardani; Byba Melda; Dhita Kurnia; Nurul Azizah (Jurnal Ners, 2020)
Introduction: Living in the prison can causing anxiety to the prisoner. The major factor of anxiety is feeling worry their society won’t accept them again a lot of people stay away from ex-prisoner. logotherapy paradoxical intention session 1 can effect anxiety prisoner in LAPAS Kediri.  The purpose of this study is to determine the effect of paradoxical intention session 1 on the anxiety in LAPAS Kediri.Methods: The design of this study was pre-experimental with a one-group pretest posttest design approach. The population studied were detainees who were in LAPAS Kediri, totalling 109 people, with a random sampling technique obtained by a sample of 78 people. The independent variable paradoxical intention logotherapy session 1 with dependent variable anxiety. Collected data using questionnaire. Data analysis using the Wilcoxon test at α = 0.05.Results: The results of the study before logotherapy showed that the majority of respondents in a panic situation were 33 respondents (42.3%) and after logotherapy showed that the fraction in severe anxiety were 18 respondents (23.1%). The results of the analysis, p-value (0.000) < (0.05), it means there is an effect of paradoxical intention session 1 on the anxiety of prisoner in LAPAS Kediri.Conclusion: Anxiety was not significant caused of age, education, length of detention, and logotherapi given as session 1, lenght of administration, and provider of logotherapy.